Interactions between Polyamines and Abiotic Stress Pathway Responses Unraveled by Transcriptome Analysis of Polyamine Overproducers - Marco, Francisco (Mary Ann Liebert, Inc., 2011)
Plant development and productivity are negatively regulated by adverse environmental conditions. The identification of stress-regulatory genes, networks, and signaling molecules should allow the development of novel strategies to obtain tolerant plants. Polyamines (PAs) are polycationic compounds with a recognized role in plant growth and development, as well as in abiotic and biotic stress responses. During the last years, knowledge on PA functions has been achieved using genetically modified plants with altered PA levels. In this review, we combine the information obtained from global transcriptome analyses in transgenic Arabidopsis plants with altered putrescine or spermine levels. Comparison of common and specific gene networks affected by elevation of endogenous PAs, support the view that these compounds actively participate in stress signaling through intricate crosstalks with abscisic acid (ABA), Ca(2+) signaling and other hormonal pathways in plant defense and development.